2020
DOI: 10.1126/sciimmunol.aat7117
|View full text |Cite
|
Sign up to set email alerts
|

Gut T cell–independent IgA responses to commensal bacteria require engagement of the TACI receptor on B cells

Abstract: The gut mounts secretory immunoglobulin A (SIgA) responses to commensal bacteria through nonredundant T cell–dependent (TD) and T cell–independent (TI) pathways that promote the establishment of mutualistic host-microbiota interactions. SIgAs from the TD pathway target penetrant bacteria, and their induction requires engagement of CD40 on B cells by CD40 ligand on T follicular helper cells. In contrast, SIgAs from the TI pathway bind a larger spectrum of bacteria, but the mechanism underpinning their productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 82 publications
2
53
0
Order By: Relevance
“…Interactions between CD40L expressed in T FH cells and CD40 expressed in B cells are necessary for the TD pathways. A similar process is accomplished in the TI pathways through interactions between BAFF/APRIL and three possible receptors, the transmembrane activator and calcium‐modulating cyclophilin ligand interactor (TACI), the BAFF receptor, and B cell maturation antigen expressed in B cells 47,48 . Of these possible receptors of BAFF and APRIL, TACI has been recently identified as indispensable in the intestinal TI pathways 48 .…”
Section: Generation Of Intestinal Secretory Igamentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between CD40L expressed in T FH cells and CD40 expressed in B cells are necessary for the TD pathways. A similar process is accomplished in the TI pathways through interactions between BAFF/APRIL and three possible receptors, the transmembrane activator and calcium‐modulating cyclophilin ligand interactor (TACI), the BAFF receptor, and B cell maturation antigen expressed in B cells 47,48 . Of these possible receptors of BAFF and APRIL, TACI has been recently identified as indispensable in the intestinal TI pathways 48 .…”
Section: Generation Of Intestinal Secretory Igamentioning
confidence: 99%
“…A similar process is accomplished in the TI pathways through interactions between BAFF/APRIL and three possible receptors, the transmembrane activator and calcium‐modulating cyclophilin ligand interactor (TACI), the BAFF receptor, and B cell maturation antigen expressed in B cells 47,48 . Of these possible receptors of BAFF and APRIL, TACI has been recently identified as indispensable in the intestinal TI pathways 48 . This TACI‐mediated intestinal TI pathways induces intestinal IgA + ASCs independent of the GCs and can elicit specific IgA responses to gut microbes 48 .…”
Section: Generation Of Intestinal Secretory Igamentioning
confidence: 99%
“…Bacteroides fragilis produces a surface polysaccharide that promotes IgA binding and facilitates mucus layer colonization [6] and the mucin-degrader Akkermansia muciniphila induces host IgA and IgG responses [7]. Other studies have suggested that low-affinity IgA contributes to microbiota maintenance, while high-affinity IgA acts on pathogens to promote clearance and inhibit virulence [8][9][10][11][12][13][14][15]. Pathobionts are members of the microbiota that are typically harmless under homeostatic conditions but can drive disease given certain environmental stimuli [16].…”
Section: Introductionmentioning
confidence: 99%
“…We refer to the sorted IgA bound bacteria as the IgA+ fraction, the sorted unbound bacteria as the IgA-fraction, and the sample before sorting as the pre-sort sample. IgA-Seq has been used to uncover antibody targeting of taxa by both T-cell dependent and T-cell independent pathways [7,10,12,21,22], as well as differential binding of taxa during disease. IgA-Seq was first described by Palm et al to identify taxa differentially bound by IgA in inflammatory bowel disease (IBD) patients [17] and was adapted by Kau et al to identify increased binding of Enterobacteriaceae by IgA in malnourished infants [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation